2023
DOI: 10.1038/s42003-023-04419-8
|View full text |Cite
|
Sign up to set email alerts
|

Global patterns of tree density are contingent upon local determinants in the world’s natural forests

Abstract: Previous attempts to quantify tree abundance at global scale have largely neglected the role of local competition in modulating the influence of climate and soils on tree density. Here, we evaluated whether mean tree size in the world’s natural forests alters the effect of global productivity on tree density. In doing so, we gathered a vast set of forest inventories including >3000 sampling plots from 23 well-conserved areas worldwide to encompass (as much as possible) the main forest biomes on Earth. We ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…The finding on tree density in Kaiti watershed is similar to findings by other studies (Akpalu et al, 2019;Baul et al, 2013;Endale et al, 2017;Jordan et al, 2016;Madrigal-gonzález et al, 2023) that tree density on farms vary from region to region. Baul et al (2013) in their study on agrobiodiversity in Nepal found peak tree density of 226 trees per hectare on farms less than 0.25 hectares and lowest tree density of 165 trees per hectare on farms between 0.26 to 0.5 hectares.…”
Section: Tree Density On Farms In Kaiti Watershedsupporting
confidence: 90%
“…The finding on tree density in Kaiti watershed is similar to findings by other studies (Akpalu et al, 2019;Baul et al, 2013;Endale et al, 2017;Jordan et al, 2016;Madrigal-gonzález et al, 2023) that tree density on farms vary from region to region. Baul et al (2013) in their study on agrobiodiversity in Nepal found peak tree density of 226 trees per hectare on farms less than 0.25 hectares and lowest tree density of 165 trees per hectare on farms between 0.26 to 0.5 hectares.…”
Section: Tree Density On Farms In Kaiti Watershedsupporting
confidence: 90%
“…4). The disconnect between tree density with climate along the latitudinal gradient due to interactions with soil fertility and tree size (Madrigal‐Gonzalez et al 2023) may have influenced the signal of tree density on richness patterns. Multivariate mixed models revealed that the interaction between tree height and density may be more important in explaining gliding species richness than tree density alone (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Neotropical rainforests, in contrast, have shorter trees, with wider crowns than those in Southeast Asia (Larjavaara 2014). Tree density patterns also show a decoupling with climate across the latitudinal gradient due to filtering imposed by interactions with soil fertility and tree size, leading to peaks in density at different latitudes (Madrigal‐Gonzalez et al 2023). The decoupling of tree height and density patterns from the latitudinal diversity gradient may have implications for species diversification rates and linked diversity patterns for vertebrate species associated with arboreal habitats.…”
Section: Introductionmentioning
confidence: 99%